Aktivitas Enzim Nitrat Reduktase Kedelai Kultivar Burangrang akibat Variasi Kadar Air Tanah pada Awal Pengisian Polong - Junica Fitriana; Krispinus Kedati Pukan; Lina Herlina (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2009)
An experiment has been conducted from February 2008 to April 2008. The objective of this research was to analize the influence of a variety of water levels to the activity of nitrate reductase enzyme (NRA) and the production of soybean (Glycine max) var. Burangrang, and to analize the correlations between the NRA and the production. Cultivar Burangrang was the main subject of the experiment. The application of the treatment was followed by the complete random design consisting of one factor with three replicates. The factor was the water levels of field capacity, 90%, 70%, 50%, 30%, and 10% of the field capacity. Every replicate consisted of 8 treatment units, and thus the whole of treatment units were 144. The water level treatment was given once per day. NRA is calculated based on the amount of nitrite produced from an assay. Nitrate was reacted using 1% sulfanilamide in 3N HCL and 0.02% napthylethylendiamide. The color was then determined using spectrophotometer at 540 nm. The result of the research indicated that the administration of water at 90% of field capacity resulted in the highest average of NRA due to good water efficiency. The best average of water efficiency for production was obtained from the variety of water quality of 70%. So it can be concluded that variety of water quality had significant influence to NRA and production. NRA had positif correlation with production. Key words: activities nitrate reductase, soybean, water quality.